Communication and Collaboration between School and Family for Addressing Bullying - J. Stamatis, Panagiotis; N. Nikolaou, Eleni (International Journal of Criminology and Sociology, 2016)
School and family are the main socializing agents for children. Therefore, effective communication and collaboration between these contexts is essential, although sometimes there are barriers to school-family partnership, particularly when they try to play a more active role in the educational process. It is widely recognized that parent involvement in school has successful contributions to student school outcomes. Moreover, It is crucial for addressing effectively bullying, as it is a problem student behaviour in Greek society as well. In this context, the present research aims to explore teachers’ views about family-school communication and collaboration regarding the extent to which they address effectively bullying. 150 primary education teachers from public schools in Rhodes participated in this research, which conducted in 2015. Results show that teachers endorse the importance of school-family collaboration for addressing bullying. In addition, they consider this collaboration important, as it has an important influence on children’s attitudes to school, and their behaviour in school environment. Furthermore, they suggest that school-family collaboration may improve students’ social skills, which can enhance their emotional development and reduce their social isolation from the peer group. Finally, they assert that school-family collaboration can empower children’s relationship with their parents and teachers, and in the long term it can contribute in enhancing their school achievement.